De que lado você mora?: um estudo sobre segregação urbana em Montes Claros 1926-2019 - Anne Caroline Veloso de Almeida (2020)
The research focuses on the City of Montes Claros/MG, part of the Minas Gerais' north Mesoregion, and study the importance of the Central Railway of Brazil of the North of Minas on the development, industrialization and consolidation of the particular socioeconomic conditions and segregation in the city. Historically, the construction of the railway branch that connected the station of Corinto to Montes Claros and, later, the expansion of the railway connections, boosted the development process of the region, mainly in the administrative and commercial areas, turning Montes Claros into a reference in the North of Minas Gerais. However, despite the importance of the railway in Montes Claros, the transportation policy implemented in the 20th century and, consequently, the urban transformation that occurred with the opening of roads and the use of individual and collective motor vehicles as preferred modes of transport, induced changes in the relations established between city residents and the train. Consequently, in 1996, the railroad in Montes Claros started to be used exclusively for cargo transportation. Although the route of the train that runs through the urban fabric in the North-South direction was maintained, this change caused transformations in the daily life of the residents of the city. Nevertheless, even though the railway connects the city in the North-South direction, there are rupture situations in the urban network and distinct socioeconomic conditions between the East and West areas. Hence, in the current context, the railway negatively influences the intensification of socioeconomic segregation conditions in Montes Claros. Under this condition, the contrasts between the areas fragmented by the line incite interest in analyzing the dichotomies existing between its extremes. Therefore, the general objective of this dissertation is to analyze the role of the railway as an infrastructure of improvement of urban space and social segregation in Montes Claros. For that purpose, qualitative research was used through document analysis, bibliographic and empirical research by field visits.